Efficacy and Safety of Vaginal Misoprostol for Cervical Ripening and Labour Induction in Late Pregnancy - Nigger, Most Nasrin; Akter, Sheuly; Zahan, Ummul Nusrat; Begum, Fatema (KYAMC Journal, 2021)
Background: Induction of labor is its intentional initiation before spontaneous onset, with the aim of vaginal birth which is safe for mother and newborn. The well documented effectiveness of misoprostol in several gynecological and obstetric applications has resulted in enthusiasm for its use. Objective: To see the efficacy and safety vaginal Misoprostal for cervical ripening and labour induction in late pregnancy. Materials and Methods: This single center clinical trial was carried out in the Department of Obstetrics and Gynaecology at Khwaja Yunus Ali Medical College and Hospital in Sirajgonj, Bangladesh from June 2019 to May 2020 for a period of one year. A total of 90 women requiring indicated induction of labour with an unfavourable cervix (Bishop score ≤ 4) were included in the study. They were randomly divided into two groups: 53 women induced with intravaginal misoprostol (Group I) and 37 women induced with transcervical Foley catheter (Group II). Results: Spontaneous vaginal delivery was 35(66.0%) in misoprostol group and 15(40.5%) in Foley catheter group. Caesarean section was higher in Foley catheter group than misoprostol group (37.8% vs 18.9%). The mean birth weight, APGAR score 1 minute, 5 minute, admission in neonatal intensive care unit and meconium aspiration syndrome were not statistically significant between two groups (p>0.05). Only one baby was died in Foley catheter group, but the difference was not statistically significant between two groups (p>0.05). Conclusion: The present study suggests intravaginal Misoprostol results in a shorter induction to delivery time, a reduction in the rate of caesarean delivery. KYAMC Journal.2021;12(02): 78-83